The study of relationship of job satisfaction, organization commitment and turnover intention towards person-organization fit: a case study at Pernec Corporation Berhad / Zalikha Esa - Esa, Zalikha (2011)
The main purpose of this study is to explore the relationship of job satisfaction, organization commitment and turnover intention towards person-organization fit at Pernec Corporation Berhad. The methodology of this study is using one hundred respondents, which we can see how many respondents that give responds towards the questionnaire that will be distribute later. The data will be interpreted by using SPSS. This is demonstrated in the finding that those who do not fit their organization tend to look for work elsewhere. The researcher proposed a few recommendations to Pernec Corporation Berhad that should be considered for its future long term planning. The statistic will be used is frequency analysis to determine level of person organization fit. Pearson correlation analysis will be used to identify the relationship between dependent variables and independent variables. To determine which factor influence the most towards person-organization fit, multiple regression analysis will be used.